Decreased bone mineral density and associated factors in severe haemophilia A patients: A case-control study - Ekinci, Omer; Demircioglu, Sinan; Dogan, Ali; Merter, Mustafa; Yildiz, Saliha; Demir, Cengiz (Wiley, 2019)
Introduction Haemophilia patients may exhibit lower levels of bone mineral density (BMD) than the general population for a variety of reasons. Aim We aimed to investigate decreased BMD in people with severe adult haemophilia A (PWH) living in eastern Turkey, and to evaluate the related potential risk factors. Methods The study included 41 PWH and 40 healthy volunteers. Dual-energy x-ray absorptiometry (DXA) was used to measure the BMD. Blood tests and body mass index (BMI) were recorded. The Functional Independence Score in Hemophilia (FISH) test was used to measure functional ability status. Results There was a significant difference between the PWH and control groups with respect to femoral neck and total hip BMD (in g/cm(2)), but the difference for lumbar spine was not significant (P = .017, P < .001, P = .071, respectively). In PWH, patients under 50 years of age, 19.4% were found to have lower than expected BMD levels for their age, while 27.8% showed low normal levels. In PWH, osteoporosis was found in 60% of the patients over 50 and osteopenia in 20%. Vitamin D insufficiency and deficiency were present in 63.4% of the PWH, significantly higher than the control group (37.5%; P < .001). Conclusion The results indicated that the decrease in BMD was significantly greater in patients with severe haemophilia A than in the normal healthy population. This reduction was correlated with BMI, vitamin D and low functional ability status. However, in multivariate analysis, none of these was a strong independent risk factor.
Keywords: bone mineral density; haemophilia; osteopenia; osteoporosis